Banana Bunchy Top Virus Molecular Confirmation and DNA-S Phylogenetic of some Banana Isolates from Indonesia - Lia Hapsari; Ruth Feti Rahayuniati; Siti Subandiyah (Bogor Agricultural University, Indonesia, 2023)
This study was aimed to confirms the Banana Bunchy Top Virus (BBTV) infection of ten banana accessions from Indonesia through PCR assay using primer of BBTV coat protein (CP) gene, also the sequences characteristics and phylogeny. Preliminary morphological results showed five acessions were positively infected with slight to severe intensity symptoms i.e. Pisang Berlin, Candi, Billa, Morosebo, and Mas Kripik; and five accessions were symptomless i.e. M. acuminata var. rutilifes and M. balbisiana, Pisang Ebung, Madu and Moseng. However, PCR results qualitatively confirms that all accessions were positively infected. Two sizes of amplicons were identified. Pisang Candi isolate was showing ±500 bp amplicons, whereas the others were ±1000-1100 bp. The total aligned and selected BBTV CP sequences of 36 accessions (bananas and other host species) was 450 nt. It was considered highly conserved (85.55%), low G+C content (41%), and high genetic similarities (92.47 to 100%). Phylogenetic analysis delineates isolates into two large groups, i.e. the Asian group (East Asia and South-east Asia) and the South Pacific group (South Asia, Africa and the Pacific). The findings of this study are usefull for broader applicability of further banana breeding program particularly for mitigation, selection and evaluation of banana with BBTV resistance.